THE INFLUENCE OF FEAR OF MISSING OUT (FOMO) AND HEDONIC SHOPPING ON IMPULSE BUYING WITH SELF-CONTROL AS A MODERATING VARIABLE AMONG STUDENT SHOPEE USERS (A CASE STUDY OF STUDENTS FROM THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITAS NEGERI GORONTALO, CLASS OF 2022) - Aditya Febriansyah Abullah; Melan Angriani Asnawi; Ramlan Amir Isa (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effect of Fear of Missing Out (FOMO), hedonic shopping, and self-control on impulse buying among students who use Shopee, as well as to examine the role of self-control as a moderating variable. This research uses a quantitative approach with a survey method involving students of the Faculty of Economics and Business, Universitas Negeri Gorontalo, class of 2022, as respondents. Data collection was conducted using questionnaires distributed through forms and Google Forms. Data analysis was carried out using SPSS and SEM-PLS 4.1 to test the relationships among variables. The results show that Fear of Missing Out (FOMO) and hedonic shopping have a positive effect on impulse buying. This indicates that digital social pressure and pleasure-driven motivation are the main factors encouraging students to engage in impulsive purchases. In contrast, self-control does not affect impulse buying, suggesting that students’ ability to regulate themselves is not yet strong enough to reduce impulsive consumption behavior. This condition is influenced by the characteristics of students who do not yet have a stable income, so self-control has not developed optimally in financial management due to the absence of income.